2013
DOI: 10.2478/ssa-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and distribution of barium and strontium in profiles of podzolic soils

Abstract: The study was aimed at determining the content, distribution and mobility of barium and strontium in various forest podzol soils. Samples with a wide range of chemical and physical properties were collected from typical uncontaminated soils of south-western Poland. The total metal content in the analyzed soils was considered as the geochemical background thanks to the natural features of the study site. Sequential chemical extraction procedure were used to provide information on the mobility and bioavailabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The geochemical association of Cu and Zn, with a coefficient of 0.61, has been associated with human activities, especially by the application of agrochemicals, which indicated that these elements were deposited from the anthropogenic sources (Iyaka & Kakulu, 2009), because no known geogenic sources were observed for the contribution of this type of association in the study area. A very strong correlation was obtained between Ba and Sr (0.75), and both of the elements have a strong affinity to bind soil particles (Jeske, 2013). In contrast to the synergism of other elements, Ba and Zr (āˆ’0.54) were negatively correlated, indicating two different sources.…”
Section: Resultsmentioning
confidence: 99%
“…The geochemical association of Cu and Zn, with a coefficient of 0.61, has been associated with human activities, especially by the application of agrochemicals, which indicated that these elements were deposited from the anthropogenic sources (Iyaka & Kakulu, 2009), because no known geogenic sources were observed for the contribution of this type of association in the study area. A very strong correlation was obtained between Ba and Sr (0.75), and both of the elements have a strong affinity to bind soil particles (Jeske, 2013). In contrast to the synergism of other elements, Ba and Zr (āˆ’0.54) were negatively correlated, indicating two different sources.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately this was not analysed when samples were collected some years ago. Moreover, during alternating phases of seasonal reducing conditions, Ba compounds can be dissolved and consequently Ba adsorbed by clays, Fe/Mn nodules and also plant roots (Magalhaes et al 2012;Jeske 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Ba content of soils in semiarid sub-tropical regions is about 400 to 1000 mg/kg, compared to maximum values of 2000-3000 mg/kg in humid tropical regions (Aubert and Pinta 1971). In podzolic soils in Poland the content is 85 to 410 mg/kg (Jeske 2013). According to USEPA data, the mean value for world soils is 430 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…where EDI = estimated daily trace element intake of the population in mg/day or per body weight (kg) and RfD o = oral reference dose (i.e., Cd, Mo, Cu, Zn, B and strontium (Sr) were 0.005, 0.04, 0.3, 0.001, 0.2 and 0.6 mg/kg/day, respectively) (USEPA 1992a;1992b;2004;2005;2013). A vegetable is presumed safe for consumption if HQ <1, while HQ>1 indicate high health risk.…”
Section: šøš·š¼ š‘…š‘“š·Omentioning
confidence: 99%
“…amount and availability of non-essential trace elements in soils to soil acidity, organic matter content, precipitation, and leaching (Jeske 2013;Ermokhin et al 2019). With regards to essential and non-essential trace elements in soils, the concentrations reported in this study were within the acceptable range (Haluschak et al 1998;CCME 1997;2005;2007;2013;2015) and thus, there was no soil trace element phytotoxicity effect at the end of the 5 th -year of the study.…”
Section: Soil Chemical Elementsmentioning
confidence: 99%